Prevalence and Severity of Injuries in Patients Following Road Traffic Accidents: A Medicolegal Aspect - Inayatullah Magsi, Shahla Imran, Pardeep Kumar, Ishtiaque Ali Langah, Nadia Aslam, Rubina Salma Yasmin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malaria is an arthropod-borne disease caused by Plasmodium. Malaria is a significant public health challenge with about 3.3 billion human lives at risk in 97 countries with two hundred million estimated malaria cases and 600,000 fatalities. Timely diagnosis can prevent disease spread, loss of human lives, and its harmful impact on the economy therefore malaria diagnosis by automated hematology analyzer is of great value. Objective: To assess identification of scattergram abnormalities in malaria samples and to compare its performance with Microscopy, RDTs & PCR. Study Design: Descriptive and cross-sectional study Place and Duration of Study: Department of Pathology, Liaquat University of Medical & Health Sciences Jamshoro, 06 months from May 2020 to October 2020. Methodology: Eighty seven malaria suspected samples were included. CBC performed on Sysmex XN1000i followed by Microscopy of thin blood film, RDTs by using STANDARDTM Q Malaria P.f/Pan Ag Test, DNA extracted by QIAamp DNA mini kit, PCR performed by GenoAmp Real-time qPCR Malaria. Results: The median age of patients was 24+13.93 years. WDF Scattergram abnormalities were observed in 95.4 %of samples with sensitivity of 97.6% and specificity of 100% respectively. PPV was 100% and NPV was 99.8%. 96.4% of patients were malaria positive by microscopy. ICT was positive in 96.6% of samples while PCR confirmed plasmodium presence in 97.7% samples. Conclusion: Automated hematology analyzer provides high sensitivity and specificity for malaria diagnosis. The Sysmex XN-1000i can detect certain abnormalities in WDF scattergrams in malaria patients. As a result, the appearance of an abnormal WDF scattergram in a patient with a history of febrile illness, aids the pathologist in confirming a malaria diagnosis.